2000
DOI: 10.1128/jvi.74.5.2333-2342.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Coronavirus Mouse Hepatitis Virus Strain A59 Small Membrane Protein E

Abstract: The small envelope (E) protein has recently been shown to play an essential role in the assembly of coronaviruses. Expression studies revealed that for formation of the viral envelope, actually only the E protein and the membrane (M) protein are required. Since little is known about this generally low-abundance virion component, we have characterized the E protein of mouse hepatitis virus strain A59 (MHV-A59), an 83-residue polypeptide. Using an antiserum to the hydrophilic carboxy terminus of this otherwise h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
204
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(223 citation statements)
references
References 48 publications
14
204
1
2
Order By: Relevance
“…4 E protein may also be involved in determining the virus budding site at the endoplasmic reticulum-Golgi intermediate compartment membrane (ERGIC). 5 E protein is important for virion morphology and virus production. 6,7 Recently it was demonstrated that the E proteins of both MHV-CoV and SARS-CoV exhibit viroporin activity.…”
Section: Introductionmentioning
confidence: 99%
“…4 E protein may also be involved in determining the virus budding site at the endoplasmic reticulum-Golgi intermediate compartment membrane (ERGIC). 5 E protein is important for virion morphology and virus production. 6,7 Recently it was demonstrated that the E proteins of both MHV-CoV and SARS-CoV exhibit viroporin activity.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, by analogy to the E viroporin of the mouse hepatitis coronavirus, another oligomeric protein which possesses an amphipathic α-helix, NS4B might form membrane-integral pores inducing membrane curvature. 116,117 (2) The recruitment of cell factors such as Arfs (ADPribosylation factors), which contain an N-terminal amphipathic helix or proteins containing BAR (Bin-Amphiphysin-Rvs) domains with a characteristic banana-like structure, might deform membranes. 118,119 (3) The lipid composition of the membrane itself might directly trigger membrane curvature.…”
Section: Biogenesis Of the Membranous Web: Remodeling Of Intracellulamentioning
confidence: 99%
“…This protein is generally a minor virion constituent. It is largely embedded within the viral membrane and only its hydrophilic carboxy terminus protrudes inside the virion [8,9].…”
Section: Introductionmentioning
confidence: 99%